Efektifitas Pelumasan Dalam Menurunkan Risiko Kerusakan Mekanis Pada Mesin Bubut - Bangun Subekti; Romiyadi Romiyadi; Yudi Dwianda (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Lubrication plays a crucial role in maintaining the performance and reliability of lathes,particularly in mechanical systems operating under high pressure and friction. Without adequatelubrication, friction between metal components increases, leading to wear, excessive heat, andultimately mechanical failures that can disrupt the continuity of production processes. This studyaims to examine the effectiveness of lubrication in reducing the risk of damage to lathes, with afocus on the types of lubricants used, lubrication methods, and the frequency of their application.The research was conducted through a literature review approach, referring to various scientificand technical sources that discuss lubrication practices in the manufacturing industry. The findingsindicate that an appropriate lubrication system can significantly extend the service life ofmachines, reduce maintenance costs, and improve operational efficiency. Therefore, a soundunderstanding of lubrication principles and practices is essential for comprehensive lathemaintenance.